Citizen’s science approach to climate smart and nutrition sensitive seed value chains for food and nutrition security in Uganda and Ethiopia - Recha, Tobias; Mohammed, Jemal; Otieno, Gloria Atieno (Bioversity International, 2020)
Local communities currently have limited access to information and the diversity of planting materials that would allow them to diversify their production systems to cope with unpredictable weather and stabilize their livelihoods. There are currently limited and scattered mechanisms in place to share and increase the diversity of farmers’ varieties beyond the local level. Establishing new community seed banks and linking them with the existing ones will create an effective network, which will allow the national system to monitor the status of on-farm conservation and enhance the flow of seeds between them. This project ‘Citizen’s science approach to climate smart and nutrition sensitive seed value chains for food and nutrition security in Uganda and Ethiopia’ aims to improve farmers’ adaptation to climate change and enhance food and nutrition security by increasing the availability of quality, diverse and adapted seeds within local communities through participatory varietal evaluation using a crowdsourcing approach and innovative seed value chains.